Clinical evidence of acupuncture for luteinized unruptured follicle syndrome: a systematic review and meta-analysis of randomized controlled trials - Zhang, Ruifang; Lin, Guangyao; Wang, Wei (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to systematically assess the efficacy of acupuncture in women with luteinized unruptured follicle syndrome (LUFS) based on existing randomized controlled trials (RCTs).MethodsA search of eight databases and one clinical trial database was conducted on May 3, 2025, to identify relevant RCTs examining the benefits of acupuncture for LUFS. The clinical outcomes of interest included two primary outcomes and five secondary outcomes. Forest plots were used to illustrate the pooled results, and sensitivity analyses were performed to verify the robustness of the evidence. Subgroup analysis was conducted to investigate whether the effect of acupuncture on the primary outcomes was related to the number of acupoints used per treatment. In addition, Begg’s and Egger’s tests were conducted to quantitatively examine publication bias among the studies.ResultsA total of 15 RCTs from China involving 1,030 participants with LUFS were included. According to the pooled results, acupuncture intervention effectively increased the ovulation rate by 25% [risk difference (RD) = 0.25, 95%CI = 0.21–0.30, p < 0.00001] and the pregnancy rate by 22% (RD = 0.22, 95%CI = 0.16–0.28, p < 0.00001) compared with the control group. Moreover, acupuncture treatment was more conducive to improving the luteinizing hormone levels [mean difference (MD) = 3.76, 95%CI = 2.27–5.25, p < 0.00001], the estradiol levels [standardized MD (SMD) = 0.47, 95%CI = 0.31–0.63, p < 0.00001], the progesterone levels (MD = 1.50, 95%CI = 1.09–1.91, p < 0.00001), the resistance index (MD = −0.07, 95%CI = −0.09 to −0.05, p < 0.00001), and the pulsatility index (MD = −0.10, 95%CI = −0.15 to −0.06, p < 0.00001) of the ovarian artery. Subgroup analysis indicated a higher ovulation rate with stimulation of more than six acupoints (28%) compared with six or fewer acupoints (19%); however, there was no notable association between the number of acupoints and the pregnancy rate (22% vs. 23%). Furthermore, sensitivity analyses confirmed the robustness of the results, while both Begg’s and Egger’s tests indicated no significant publication bias across studies.ConclusionsThis pooled evidence from Chinese RCTs reveals that acupuncture is a promising complementary therapy for LUFS. However, these findings might not be generalizable outside China, and most trials exhibited deficient methodological reporting. Therefore, further research studies with more rigorous designs and larger sample sizes are needed to confirm the efficacy of acupuncture for LUFS.Systematic review registrationwww.crd.york.ac.uk, identifier CRD420251062225.